MICHELS SYNDROME IN A BRAZILIAN GIRL BORN TO CONSANGUINEOUS PARENTS - Guionalmeida, M. L.; Rodini, ESO (Wiley-Blackwell, 1995)
We report on a Brazilian girl born to consanguineous parents and presenting with craniosynostosis, telecanthus, blepharophimosis, blepharoptosis, epicanthus inversus, cleft lip and palate, skeletal defects, and hearing loss. This combination of anomalies appears to constitute the Michels syndrome. (C) 1995 Wiley-Liss, Inc.
Keywords: CRANIOSYNOSTOSIS; EYELID ABNORMALITIES; HYPERTELORISM; CLEFTING; MICHELS SYNDROME